New host record of Sclerotium rolfsii causing crown and root rot on Pseudogynoxis benthamii - Rivera, Marta Carolina (2018)
Fil: Rivera, Marta Carolina. Instituto Nacional de Tecnología Agropecuaria. Instituto de Floricultura. Hurlingham, Buenos Aires, Argentina.